The Administrative and Ethical Considerations of Climate Resilience: The Politics and Consequences of Climate Change. (2nd January 2022) - Alibašić, Haris
Abstract : Public servants responsiveness and administrative responsibilities to their constituents in local communities are identified through the set of ethical standards predominantly resulting in good governance. Some researchers and practitioners in the field of integrity and ethics concur with the premise of administrative responsibility and responsiveness operating under holistic approaches to understanding climate resilience. This analysis contends with the traditional views of the theory of social choice and administrative burden to stipulate a suitable ethical framework and understanding of ethics in considering climate resilience. The research takes into consideration the principles and structure of moral expectations and measurable outcomes related to climate resilience through the Quadruple Bottom Line lens. The good governance in resilience is explored using an exploratory data analysis of local governments through resilience planning supported by the Rockefeller Foundation, which funded 100 Resilient Cities initiative. The sample size consisted of thirty cities with the obtainable resilience or climate actions plans and a review of their governance efforts through those documents and detailed plans. The research offers a preliminary report of the ongoing efforts in cities and regions to combat climate change, coupled with the ethical considerations and administrative responsibility to frame the administrators' role in deliberation to climate resilience. The research findings assert a prototype ethical framework for review by administrators to augment administrative responsiveness to climate change threats and increase climate resilience.